Autophagy modulates growth and development in the moss Physcomitrium patens - Pettinari, Georgina; Finello, Juan; Plaza Rojas, Macarena; Liberatore, Franco; Robert, Germán; Otaiza-González, Santiago; Velez, Pilar; Theumer, Martin; Agudelo-Romero, Patricia; Enet, Alejandro; González, Claudio; Lascano, Ramiro; et al. (Frontiers in Plant Science, 2022)
Physcomitrium patens apical growing protonemal cells have the singularity that they continue to undergo cell divisions as the plant develops. This feature provides a valuable tool to study autophagy in the context of a multicellular apical growing tissue coupled to development. Herein, we showed that the core autophagy machinery is present in the moss P. patens, and characterized the 2D and 3D growth and development of atg5 and atg7 loss-of-function mutants under optimal and nutrient-deprived conditions. Our results showed that 2D growth of the different morphological and functional protonemata apical growing cells, chloronema and caulonema, is differentially modulated by this process. These differences depend on the protonema cell type and position along the protonemal filament, and growth condition. As a global plant response, the absence of autophagy favors the spread of the colony through protonemata growth at the expense of a reduction of the 3D growth, such as the buds and gametophore development, and thus the adult gametophytic and reproductive phases. Altogether this study provides valuable information suggesting that autophagy has roles during apical growth with differential responses within the cell types of the same tissue and contributes to life cycle progression and thus the growth and development of the 2D and 3D tissues of P. patens.